The influence of indoor environment in respiratory health and quality of life of older people living in elderly care centers - Mendes, Ana Sofia (2018)
Tese de doutormaneto em Ciências Biomédicas, apresentada ao Instituto de Ciências Biomédicas Abel Salazar da Universidade do Porto, 2016